Kajian Moneter Terhadap Nilai Tukar Nelayan Tangkap di Provinsi Aceh - Faris Mubarak; Leli Putri Ansari (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2023)
This study examines the effect of monetary factors on fisherman exchange rates in Aceh Province. The financial review includes the household consumption index for fishing fishermen, diesel fuel, and the human development index. This study used time series data for 2012-2020, and data analysis was carried out using multiple linear regression analysis. The results showed that the household consumption index of fishing fishermen has a negative but insignificant effect on the exchange rate of fishing fishermen in Aceh Province. The cause is the habit of capturing fishermen to consume beyond their means (especially consuming non-food goods such as luxury goods), which impacts high inflation rates. Meanwhile, the price of diesel fuel has a positive but insignificant effect on the exchange rate of fishermen in Aceh Province. The reason is due to the limited use of subsidized diesel fuel provided by the government so that when the price of diesel rises or falls, fishermen will still buy up to the limit provided by the government, and the price of diesel fuel is an indispensable need. Furthermore, the human development index negatively and significantly influences the exchange rate of captured fishermen in Aceh Province. Based on the human development index in the education sector, fishermen in Aceh Province still need higher education, so they cannot manage their lifestyle and finances properly even though their income is high.